"Everyone thinks it's someone else's responsibility": training for sexual health doctors. (8th December 2017) - Unknown
Abstract : With sexual health service commissioning beset by intense financial pressures and split responsibilities, the specialties of genitourinary medicine and sexual and reproductive health face an uncertain future, finds Caroline White